Marine-Steroid Derivative 5α-Androst-3β, 5α, 6β-triol Protects Retinal Ganglion Cells from Ischemia–Reperfusion Injury by Activating Nrf2 Pathway - Longxiang Sheng; Bingzheng Lu; Hui Chen; Yun Du; Chen Chen; Wei Cai; Yang Yang; Xuyan Tian; Zhaofeng Huang; Wei Chi; Suizhen Lin; Guangmei Yan; et al. (Marine Drugs, 2019)
High intraocular pressure (IOP)-induced retinal ischemia leads to acute glaucoma, which is one of the leading causes of irreversible visual-field loss, characterized by loss of retinal ganglion cells (RGCs) and axonal injury in optic nerves (ONs). Oxidative stress and the inflammatory response play an important role in the ischemic injury of retinal and optic nerves. We focus on 5α-androst-3β, 5α, 6β-triol (TRIOL), a synthetic neuroactive derivative of natural marine steroids 24-methylene-cholest-3β, 5α, 6β, 19-tetrol and cholestane-3β, 5α, 6β-triol, which are two neuroactive polyhydroxysterols isolated from the soft coral Nephthea brassica and the gorgonian Menella kanisa, respectively. We previously demonstrated that TRIOL was a neuroprotective steroid with anti-inflammatory and antioxidative activities. However, the potential role of TRIOL on acute glaucoma and its underlying mechanisms remains unclear. Here, we report TRIOL as a promising neuroprotectant that can protect RGCs and their axons/dendrites from ischemic−reperfusion (I/R) injury in an acute intraocular hypertension (AIH) model. Intravitreal injection of TRIOL significantly alleviated the loss of RGCs and the damage of axons and dendrites in rats and mice with acute glaucoma. As NF-E2-related factor 2 (Nrf2) is one of the most critical regulators in oxidative and inflammatory injury, we further evaluated the effect of TRIOL on Nrf2 knockout mice, and the neuroprotective role of TRIOL on retinal ischemia was not observed in Nrf2 knockout mice, indicating that activation of Nrf2 is responsible for the neuroprotection of TRIOL. Further experiments demonstrated that TRIOL can activate and upregulate Nrf2, along with its downstream hemeoxygenase-1 (HO-1), by negative regulation of Kelch-like ECH (Enoyl-CoA Hydratase) associated Protein-1 (Keap1). In conclusion, our study shed new light on the neuroprotective therapy of retinal ischemia and proposed a promising marine drug candidate, TRIOL, for the therapeutics of acute glaucoma.